175 The Suitability of Autoclave and Pressure Cooker Washing Methods in Comparison to ANKOM200 to Determine Neutral Detergent Fiber Using Different Feedstuffs and Washing Solutions. (28th November 2020) - Adams, Jordan; Norris, Aaron B; Rivera, Madeline E; Batista, Luiz Fernando Dias; Tedeschi, Luis O
Abstract: The use of the in vitro gas production (IVGP) technique requires accurate determination of neutral detergent fiber (NDF) residue. However, the NDF determination using standard procedures are not always feasible for IVGP; thus requiring micro-NDF methods, which need autoclave (AC) and pressure cooker (PC) to boil the solution. A complete randomized design using a 3×3 factorial arrangement was implemented to investigate the effect of washing methods (WM: AC, PC, or ANKOM 200 ) and solution ratios (WS: 100 mL neutral detergent solution (ND), 150 mL ND, or 100 mL H2 O/g sample) to determine NDF residues, assuming ANKOM 200 and 100 mL ND/g as the standard methodology. Each factor combination was performed in triplicate with a replicate being comprised of 12 bottles or bags (two blanks and five feedstuffs in duplicate). Feedstuffs were: alfalfa hay (AH), bermudagrass hay (BH), two high-forage rations (G1 and G2), and a high-concentrate ration (FR). Following each run, bottles were filtered to obtain the NDF. Data were analyzed by diet using a random coefficients model. An interaction of WM ′ WS was present for AH and G1 (P < 0.01), G2 and FR had tendencies (P = 0.08 and 0.06, respectively), whereas BH demonstrated no interaction (P = 0.37). The PC with 100 mL or 150 mL did not differ from the standard methodology for AH, G1, G2, and FR. The BH demonstrated differences between WM and WS (P < 0.01). The PC had lower NDF residue compared to the AC and ANKOM 200, whereas H2 O had substantially greater NDF residue relative to both ND ratios. We concluded that H2 O is not a suitable substitute for ND solution regardless of the feedstuff. Both micro-NDF washing methods may be satisfactory depending on the type of feedstuff used but further investigation is required.